Essential Oils as a Resource to Support the Mental Health of Academics and Health-Care Professionals - Silva, Camila Caroline da; Berbert, Laura Vicentim; Sakalem, Marna (ID on line. Revista de psicologia, 2023)
Stressful situations, common in the current world scenario, culminate in negative impacts on the mental health. Due to the busy routines, with many hours of work and study each week, academics and health care workers are among the most affected by mood and anxiety disorders, with an increasing incidence of substance abuse. Besides psychotropic medications to combat psychosomatic disorders, other intervention possibilities with fewer reports of adverse effects can be used, such as essential oils (E.O.s). Objective: To conduct a literature review to investigate possible positive effects of selected essential oils on physical and mental impacts arising from stress and anxiety. Methods: A literature review was conducted using Google Scholar, SciELO, and PubMed databases. Original papers that contained clinical research evaluating the effects of E.O.s on physical and mental health were selected. Results: The use of essential oils, most notably lavender (8 studies), lemongrass (6 studies), bergamot (3 studies) and cypress (2 studies), demonstrated to be an effective alternative for the treatment of anxiety, stress, and depression. Conclusion: The use of essential oils is effective in the support of mental disorders and is thus of great relevance to the general well-being of academics and health care professionals.